2013
DOI: 10.4269/ajtmh.2012.12-0433
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy and Tuberculosis Co-Infection: Clinical and Immunological Report of Two Cases and Review of the Literature

Abstract: Abstract. A review of the records of patients seen between 2004 and 2011 at the Dermatology Clinic of the Sã o Paulo University Medical School showed that only two leprosy patients had been co-infected with tuberculosis (TB). One patient showed a type 1 leprosy reaction during the first 3 months of treatment of pleural TB and in the other patient, pulmonary TB was diagnosed during the first 3 months of treatment of a type 1 leprosy reaction. Both patients showed normal cellular immune response tests, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…Coinfection with M tuberculosis and M leprae was common before the availability of good antimycobacterial treatment, but is uncommon today. 102 Coinfection is usually seen in immunocompromised or immunosuppressed patients.…”
Section: Clinical Results/outcomesmentioning
confidence: 99%
“…Coinfection with M tuberculosis and M leprae was common before the availability of good antimycobacterial treatment, but is uncommon today. 102 Coinfection is usually seen in immunocompromised or immunosuppressed patients.…”
Section: Clinical Results/outcomesmentioning
confidence: 99%
“…A number of reasons have been put forth against the simultaneous occurrence of the two infections [8–11]. However studies have suggested that multibacillary (anergic form) leprosy predisposes to tuberculosis [12]. Few reasons have been put forth against the simultaneous occurrence of the two infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of the interaction between the two mycobacterial infections still remains to be clarified. Studies have suggested that leprosy, especially the anergic form, predisposes to tuberculosis [12]. It has been argued that the impaired cell-mediated response to Mycobacterium leprae of lepromatous leprosy patients would favor the advance of the more virulent pathogen Mycobacterium tuberculosis [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yearly, more than 200,000 new cases of leprosy and more than nine million new cases of tuberculosis are reported worldwide. Both of these diseases are highly prominent in Brazil, especially in the North, Northeast, and Central-West regions, with approximately 30 thousand and 700 new cases of leprosy and tuberculosis, respectively, reported yearly in the country (21) . As a result of airborne diseases, the use of facemasks with respirators (N95), the key PPE in the context of respiratory diseases, such as tuberculosis, becomes necessary (22)(23) .…”
Section: Discussionmentioning
confidence: 99%